The Influence of the Role of Case Manager and Organizational Citizenship Behavior on Patient Satisfaction at Ulin Banjarmasin Regional Hospital - Muhammad Aini; Rosihan Adhani; Titien Agustina (Cita konsultindo, 2025)
This study aims to first determine the role of Case Manager in its influence on patient satisfaction at Ulin Banjarmasin Regional Hospital, second determine the influence of Organizational Citizenship Behavior on patient satisfaction at Ulin Banjarmasin Regional Hospital, and third determine the influence of the role of Case Manager and Organizational Citizenship Behavior simultaneously on patient satisfaction at Ulin Banjarmasin Regional Hospital. Ulin Regional Hospital, BanjarmasinThe population of this study is all patients at Ulin Banjarmasin Regional Hospital who have used the facilities provided by the Case Manager during the period of 2022 to 2023, totaling 24,482 patients , so the number of samples is 24,482 respondents . This study is a quantitative study with a quantitative descriptive approach. The analysis tools used in this study include data validity and reliability tests. The hypothesis testing methods used are Kolmogorov-Smirnov, Multicollinearity Test, Autocorrelation Test and Heteroscedasticity Test,obtained in the form of conclusions obtained, namely the role of the case manager has an effect on patient satisfaction at Ulin Banjarmasin Regional Hospital , then Organizational Citizenship Behavior has an effect on patient satisfaction at Ulin Banjarmasin Regional Hospital , and the role of the case manager and Organizational Citizenship Behavior simultaneously have an effect on patient satisfaction through Organizational Citizenship Behavior . RSUD Ulin Banjarmasin . It is expected that there will be similar development research with more complete attention to other aspects as indicators of assessing factors that influence patient satisfaction. Also to use more and varied research subjects. The next research is expected to be able to increase the number of items in the questionnaire to measure more detail from each indicator, the addition of independent variables that are not in this study, as well as other newer and more contemporary dependent variables.